PENGARUH PERAYAAN TRADISI BUDAYA â€œPER-PERANâ€ PASCA LEBARAN DALAM MENINGKATKAN PENDAPATAN MASYARAKAT PESISIR DESA BANDARAN - Suhaimi; Nur Jamilah (STIE Bakti Bangsa Pamekasan, 2022)
Culture and the economy essentially have an equal position and mutually support one another. Customs or culture in the country of Indonesia vary according to the tribe in which the culture appears. One of the cultures and customs inherited from our ancestors that is still going well and continues to be carried out by the community today is the